Strata Title in Practice: Legal Review of Apartment Ownership in Pekalongan Under Law No. 20 of 2011 - Novarianti, Widiya Dwi; Bharata, Aditya Kusuma; Faiz, Muhammad; Nair, Priya; Suksawat, Kanya (Universitas Negeri Semarang, 2025)
This research discusses the juridical aspects of apartment ownership with a focus on the implementation of the provisions of the Right of Ownership over Apartment Units (HMSRS) in Pekalongan City based on Law No. 20 of 2011 on Apartments. The background of this research arises from the issue of limited land in urban areas due to rapid population growth and urbanization, which encourages the need for alternative vertical housing such as apartments. Apartments have become a solution to the housing crisis, particularly for low-income communities (MBR), but the legal implementation in the region often does not fully align with national regulations. This study highlights that the management of Rusunawa in Pekalongan City is still carried out administratively with a rental system, without granting individual ownership rights as stipulated in the law. Through a normative juridical approach, this research examines the legal provisions regarding land status and assesses the extent to which regional regulations and field practices reflect national legal principles. The research results show a discrepancy between lex superior and lex inferior, which can cause legal uncertainty for residents. This research recommends a reformulation of regional policies, an active role for the National Land Agency (BPN) in legal recognition, and the importance of increasing public legal literacy to create a fair and sustainable apartment ownership system.